2020
DOI: 10.1515/ijfe-2020-0223
|View full text |Cite
|
Sign up to set email alerts
|

Tri-frequency ultrasound as pretreatment to infrared drying of carrots: impact on enzyme inactivation, color changes, nutrition quality parameters and microstructures

Abstract: The effects of tri-frequency ultrasound as pretreatment on the peroxidase (POD) inactivation and infrared drying attributes of carrots were studied in the temperature range of 60–80 °C. Thermosonication (TS) treatment reduced 65.21, 73.33 and 81.43% POD activity after 5 min for the temperatures at 60, 70 and 80 °C, respectively, which were all higher than hot water (HW) blanching treated samples. The first-order kinetics fitted well for the POD inactivation curves. Similar retention ranges of vitamin C (VC) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The increase in a* and b* values depicts that a certain extent of non-enzymatic browning (Maillard reaction) took place due to sample exposure to hot air [40] . US and US-OD improved the brightness of samples compared to the control and aligns with the findings of Rani & Tripathy [47] and Guo et al [27] . However, untreated samples had a higher a* value (redness) than US and US-OD groups but smaller than US-ET samples.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The increase in a* and b* values depicts that a certain extent of non-enzymatic browning (Maillard reaction) took place due to sample exposure to hot air [40] . US and US-OD improved the brightness of samples compared to the control and aligns with the findings of Rani & Tripathy [47] and Guo et al [27] . However, untreated samples had a higher a* value (redness) than US and US-OD groups but smaller than US-ET samples.…”
Section: Resultssupporting
confidence: 90%
“…It is worth noticing that TFU treatment of US samples had water uptake similar to that of DFU in ethanol. Guo et al [27] , Xu et al [25] , and Zhou et al [31] have also demonstrated the positive effect of multi-frequency ultrasound on the rehydration of agro-products. Generally, ultrasound was found to improve the reconstitution of dried samples due to the rupture of cell walls [40] , [49] , [58] .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations